Relationship of deleterious oral habits and bruxism in childhood - Integrative literature review (Research, Society and Development, 2023)
Bruxism is a condition characterized by the repetitive activity of grinding or clenching teeth, generally involuntary, which occurs during sleep (sleep bruxism) or while awake (wake bruxism), and which, if associated with other deleterious oral disorders, can trigger damage to the stomatognathic system. The objective of the work is to identify the main findings in the literature on the relationship between harmful oral habits and bruxism in childhood. This work is an integrative review of the literature, in which 16 articles were selected, published in English and Portuguese, between 2013 and 2023, in the Scielo, Lilacs and Pubmed databases. The manifestation of bruxism in children can be triggered by stress, anxiety, sleep disorders, respiratory changes and bite changes. Added to this, harmful oral habits, such as non-nutritive sucking (use of pacifiers) and digital sucking, can be harmful to oral health. It was found that there is no methodological linearity between the studies carried out on the relationship between harmful oral habits and bruxism, which results in disparities between ages, gender and biopsychosocial aspects between the samples. Therefore, it is essential that protocols are created in order to standardize assessments, so that the dynamism of these disorders in different samples can be identified, and thus, it becomes possible to indicate appropriate treatment for those affected.